The Use of Therapeutic Ultrasound in the Management of Patients with Temporomandibular Disorder: A Clinical, Cross-Sectional and Quantitative Study - Iza Melo Freitas; Carlos Ricardo de Queiroz Martiniano; Marcelo Bruno Lemos de Oliveira; Thereza Cristina Farias Botelho Dantas; Patrícia Lenora dos Santos Braga; Emmanuel Arraes de Alencar Júnior; Antônio Sérgio Guimarães (Archives of Current Research International, 2025)
Background: To manage the temporomandibular disorders (TMD), one of the resources used is therapeutic ultrasound (UST). Objective: To evaluate the use of therapeutic ultrasound in individuals with temporomandibular disorders (TMD). Methods: This is a clinical study, which 42 individuals,aged 18-73 years, diagnosed with TMD were recruited. Participants then bit into a wooden spacer until they felt fatigue in the masseter muscle, with time assessed on both sides(right and left), followed by chewing gum. Subsequently,USD was applied to the masseter (at a frequency of 2.0 W=0.52W/cm² for 4 minutes) and the wooden spacer test was repeated to assess the time of fatigue in this muscle. Results: The most affected age group was up to 28 years old (52.4%), and females (73.8%) (p<0.05). Regarding the amount of fatigue, there was a decrease on the left side in the control group and on both sides in the TMD group, with a significant difference (P=0.0049) for the left side when evaluating before and after the treatment.When comparing times, the TMD group also showed the greatest reduction, (P=0.0012) for the left side. Conclusion: It is concluded that ultrasound therapy promoted immediate improvement in the tightening of the wooden spacer,causing muscle relaxation through the heat applied,reducing fatigue in the masseter muscle.